2006
DOI: 10.1096/fj.05-4875fje
|View full text |Cite
|
Sign up to set email alerts
|

S‐glutathiolation by peroxynitrite of p21ras at cysteine‐118 mediates its direct activation and downstream signaling in endothelial cells

Abstract: The highly reactive species, peroxynitrite, is produced in endothelial cells in pathological states in which the production of superoxide anion and NO is increased. Here, we show that peroxynitrite added exogenously or generated endogenously in response to exposure to an NO donor or oxidized low-density lipoproteins (oxLDL) increases p21ras activity in bovine aortic endothelial cells. The activation is not dependent on upstream elements but rather is due to direct targeting of p21ras by reversible S-glutathiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
125
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 40 publications
(63 reference statements)
7
125
1
Order By: Relevance
“…Mallis et al [12] showed that recombinant p21ras can be S-glutathiolated on the C-terminal cysteines by hydrogen peroxide and glutathione or by GSSG, but the effect on activity was not assessed. In a recent study from our lab, we found that direct oxidant-mediated S-glutathiolation of recombinant p21ras increases its activity, and that peroxynitrite formed endogenously can mediate signaling in endothelial cells in response to nitric oxide donors, ONOO − , or stimuli which produce endogenous ONOO − , such as oxidized LDL [17]. In addition, angiotensin II in vascular smooth muscle cells [6], and alpha-adrenergic stimulation [8] or mechanical stretch [18] of cardiac myocytes increase endogenous hydrogen peroxide and initiate MAP kinase and Akt signaling via p21ras S-glutathiolation.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Mallis et al [12] showed that recombinant p21ras can be S-glutathiolated on the C-terminal cysteines by hydrogen peroxide and glutathione or by GSSG, but the effect on activity was not assessed. In a recent study from our lab, we found that direct oxidant-mediated S-glutathiolation of recombinant p21ras increases its activity, and that peroxynitrite formed endogenously can mediate signaling in endothelial cells in response to nitric oxide donors, ONOO − , or stimuli which produce endogenous ONOO − , such as oxidized LDL [17]. In addition, angiotensin II in vascular smooth muscle cells [6], and alpha-adrenergic stimulation [8] or mechanical stretch [18] of cardiac myocytes increase endogenous hydrogen peroxide and initiate MAP kinase and Akt signaling via p21ras S-glutathiolation.…”
Section: Introductionmentioning
confidence: 92%
“…[17,24,25] Recombinant H-p21ras (2 μg) was loaded with a fluorescent nucleotide analogue N-methylanthraniloyl GDP (Mant-GDP), which exhibits fluorescence only when bound to the protein. The p21ras was incubated 1 h at 37°C with an excess of Mant-GDP in a binding buffer (potassium phosphate buffer (50 mM), NaCl (50 mM), MgCl 2 (5 mM) and EDTA (5 mM)) and the protein-Mant-GDP complex was purified on a PL-6 spin column.…”
Section: P21ras Activity Assaymentioning
confidence: 99%
See 3 more Smart Citations